Respon Return Pasar Modal Indonesia terhadap Kebijakan Moneter Domestik dan Asing - Aulia Yulianti Wulandari; Noer Azam Achsani; Lukytawati Anggraeni (IPB University, 2018)
Understanding the impact of external shocks on the stock market return and volatility is crucial for market participants as volatility is synonymous with risk. This paper provides comprehensive evidence on the spillover effects of the change of monetary policies from inside country and foreign origins on Indonesia stock market in the period of the time from November 2, 2012 to May 15, 2017. Used symmetric (IGARCH) and asymmetric (EGARCH and APARCH) GARCH model analysis to evaluate the impact of surprise and anticipated changes of monetary policies from inside country and foreign policies (from another ASEAN countries and leading economies, in this paper are United States, Europe, and United Kingdom). Surprise change of monetary policy is proxied by one day change in 3 months interbank offered rate, while anticipated change of monetary policy is proxied by one day change in target interest rate or policy rate. The result shows that information of the monetary policy news and Indonesia stock return is asymmetric. Indonesia stock market is only affected by foreign monetary policies. Keywords: ASEAN stock market, GARCH, Monetary policy JEL classification: C01, C50, E50